(untitled) (Journal of Economic Research & Business Administration, 2025)
The threats of financial crisis, social tension, political instability, as well as the danger of a humanitarian catastrophe are common to the entire world community, but they have a particularly strong impact on developing countries. The purpose of the article is to research current agriculture development trends in Kazakhstan in the context of the integration of the world economy and the development of guidelines for improving the state of the sector. The following general scientific methods were used in the research: the methods of analysis, synthesis and formalization; graphical methods, methods of statistical analysis, method of comparisons, analysis of dynamics and structure; method of causal and logical relationships and dependencies; SWOT analysis and minimax analysis. As a result of the research, a retrospective of the agricultural industry in Kazakhstan was considered, the climatic and geographical conditions in which it develops, as well as the degree and directions of state support were determined. The current world trends in the agricultural sector were studied and the directions of their development in Kazakhstan were determined. The research is aimed at improving the efficiency, environmental friendliness and productivity of agricultural enterprises in Kazakhstan based on a study of the initial conditions, the current state and global trends in the development of the sector. Key words: agro-industrial sector; SWOT analysis; Kazakhstan; food marketing; sustainable development.